Creating positive memory in staged experiences through sensory tools. Issue 14 (18th July 2022) - Elvekrok, Ingunn; Gulbrandsøy, Pia
ABSTRACT : This research investigates the link between the degree of sensory stimulation and positive memory in staged experiences. First, a field study on how two museums used sensory tools in their experience design was conducted. The findings showed that senses played an important role in experience evaluation. However, the actual effect was often felt on a subconscious level, making it difficult for visitors to distinguish between the importance of different senses. Taking this into account, the second study was conducted with a holistic view of the senses. Data were collected through an online survey distributed to a consumer panel asking the participants to relate to a specific experience. The findings showed a strong relationship between the sensory dimension and positive memory, in part mediated by cognitive and affective dimensions. These findings and the chosen methodology add to the growing knowledge on sensory experience design. From a practical perspective, this study offers important implications for experience providers.